Racial disparities and colorectal cancer survival in older adults with and without diabetes mellitus. Issue 12 (18th November 2014) - Waheed, Salman; Azad, Nilofer; Waheed, Sehrish; Yeh, Hsin‐Chieh
Abstract Background and Aim To investigate whether pre‐existing diabetes modifies racial disparities in colorectal cancer (CRC) survival. Methods We analyzed prospective data from 16 977 patients (age ≥ 67 years) with CRC from the Surveillance Epidemiology and End Results (SEER)‐Medicare database. SEER registries included data on demographics, tumor characteristics, and treatment. Medicare claims were used to define pre‐existing diabetes and comorbid conditions. Mortality was confirmed in both sources. Results At baseline, 1332 (8%) were African Americans and 26% had diabetes (39% in blacks; 25% in whites). From 2000 to 2005, more than half of the participants died (n = 8782, 52%). This included 820 (62%) deaths (23.8 per 100 person‐years) among blacks, and 7962 (51%) deaths (16.6 per 100 person‐years) among whites. Among older adults with diabetes, blacks had significantly higher risk of all‐cause and CRC mortality after adjustments for demographic characteristics (hazard ratio [HR], 95% confidence interval [CI]: 1.21 [1.08–1.37] and 1.21 [1.03–1.42]), respectively, but these associations attenuated to null after additional adjustments for cancer stage and grade. Among adults without diabetes, the risk of all‐cause mortality (HR [95% CI]: 1.14 [1.04–1.25]) and CRC mortality (HR [95% CI]: 1.21 [1.08–1.36]) remained higher in blacks than whites in fully adjusted models that included demographic variables, cancer stage, grade, treatments, and comorbidities. Conclusions Among older adults with CRC, diabetes is an effect modifier on the relationship between race and mortality. Racial disparities in survival were explained by demographics, cancer stage, and grade in patients with diabetes.